2002
DOI: 10.1523/jneurosci.22-22-10009.2002
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Information Is Required for Dead Reckoning in the Rat

Abstract: Dead reckoning is an on-line form of spatial navigation used by an animal to identify its present location and return directly to a starting location, even after circuitous outward trips. At present, it is not known which of several self-movement cues (efferent copy from movement commands, proprioceptive information, sensory flow, or vestibular information) are used to compute homeward trajectories. To determine whether vestibular information is important for dead reckoning, the impact of chemical labyrinthect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
147
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 168 publications
(164 citation statements)
references
References 45 publications
14
147
3
Order By: Relevance
“…Contradicting these results, however, are findings reported by Alyan and McNaughton (1999) of intact PI in hippocampectomized animals, a discrepancy that has not yet been explained. Further supporting a PI role for the hippocampus, hippocampal lesions impair angular PI by head direction cells (Golob and Taube, 1999) and vestibular lesions, which disrupt the place cell representation (Taube et al, 1996), also impair path integration (Cohen, 2000;Wallace et al, 2002).…”
Section: Pi and The Representation Of Spacementioning
confidence: 99%
See 1 more Smart Citation
“…Contradicting these results, however, are findings reported by Alyan and McNaughton (1999) of intact PI in hippocampectomized animals, a discrepancy that has not yet been explained. Further supporting a PI role for the hippocampus, hippocampal lesions impair angular PI by head direction cells (Golob and Taube, 1999) and vestibular lesions, which disrupt the place cell representation (Taube et al, 1996), also impair path integration (Cohen, 2000;Wallace et al, 2002).…”
Section: Pi and The Representation Of Spacementioning
confidence: 99%
“…Recent studies have indicated an important role for the vestibular system in path integration, as animals and humans with vestibular damage show navigational impairment in the absence of landmarks (Cohen, 2000;Slackman et al, 2002;Wallace et al, 2002). Other types of information may play a part as well, such as short-term copies of locomotor commands (efference copies) and inertial signals due to acceleration from extravestibular gravity receptors (Mittelstaedt, 1999; for review, see Berthoz et al, 1999;Etienne et al, 1996).…”
Section: Estimation Of Direction and Distancementioning
confidence: 99%
“…Although it is possible that in the early postnatal period the short returns of rat pups are guided by local cues, for longer trips at older ages it is likely that the pups are using dead reckoning, as has been suggested for adult rats (Wallace et al, 2002a(Wallace et al, ,b, 2003Whishaw & Gorny 1999;Whishaw, Hines, & Wallace, 2001). First, direct returns persisted in infra red light, in which visual cues cannot be seen.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies with adult rats have found that exploration is organized, and consists of two component spatial behaviors, piloting and dead reckoning (Wallace et al, 2002a(Wallace et al, ,b, 2003. If rats are provided with a home base in an otherwise open arena, they use the base as a center for their exploratory behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation